A tuberculosis school outbreak in China, 2018: reaching an often overlooked adolescent population. (2019) - You, N. N.; Zhu, L. M.; Li, G. L.; Martinez, L.; Lu, W.; Liu, Q.; Yang, H. T.
Abstract: Adolescents have been largely neglected from tuberculosis control efforts. In low- to medium burden settings much of the tuberculosis burden in this age group occurs from school outbreaks. We report on a large tuberculosis outbreak in adolescents from a boarding high school in Jiangsu Province, China. From March to June 2018, a tuberculosis outbreak occurred in a boarding high school. We conducted an outbreak investigation involving clinical diagnostic tests and molecular analysis to determine the outbreak origin. Cases were detected through symptom screening, tuberculin skin testing (TST), chest radiography, sputum smear, solid sputum culture and GeneXpert MTB/RIF. Mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) genotyping and spoligotyping methods were performed on Mycobacterium tuberculosis ( M. tuberculosis ) isolates to identify the outbreak origin. A total of 845 students and 131 teachers/staff attended a TST screening for tuberculosis infection. The prevalence of elevated tuberculin reactions at ≥5, ≥10 and ≥15 mm was 12.19% (119/976), 6.35% (62/976) and 3.28% (32/976), respectively. Radiographic abnormalities were present in 5.73% (56 of 976) individuals, 40 students and 16 teachers/staff. Of these, 12 students were diagnosed with confirmed tuberculosis. In total, 14 students (two index cases and 12 confirmed cases) were diagnosed and reported in the tuberculosis outbreak, an attack rate of 1.7% (14/847) among students (two index cases and 845 screened students). Results from MIRU-VNTR typing and spoligotyping analyses demonstrated that three M. tuberculosis strains belong to the Beijing family with corresponding MIRU-VNTR alleles. This school-based tuberculosis outbreak among adolescents demonstrates that transmission among individuals in this age group is common and must be prioritised. It suggests that identifying and timely diagnosis of smear-positive cases, especially in the early phase of outbreaks, is the key to preventing further spread among close contacts.